Pengaruh Periklanan Dan Kualitas Produk Smartphone Samsung Terhadap Keputusan Pembelian Konsumen - Wijaya, Kevin Cahaya; Pratomo, Anton Widio (Jurnal Informatika Kesatuan, 2022)
This study aims to find out the advertising factors and quality of Samsung Smartphone Products can influence purchasing decisions. This study used independent variables (Advertisingand Product Quality) and dependent variables (Purchase Decisions). This study was conducted in Jabodetabek, with data collection method using questionnaires distributed to 160 respondents. Research data is processed using SPSS program. The result of this study is that (1) Advertising has no positive and insignificant effect on Purchasing Decisions on Samsung Smartphones with a regression coefficient value of 0.019 and has a signification value of 0.150. (2) The quality of Samsung Smartphone Products positively and significantly affects the Purchase Decision with a regression coefficient value of 0.617 and has a significant value of 0.000. (3) Advertising and Quality of Samsung Smartphone Products positively and significantly affects The Buying Interest in Vitatonic Sangobion products with a calculated F value of 2679,234 and greater than F table 3.07 with a significance value of 0.000 Keywords: Advertising, Product Quality and Purchasing Decisions